2022
DOI: 10.17309/tmfv.2022.3s.20
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant Analysis: Age-Specific Features of Motor Fitness of Girls Aged 7 to 9

Abstract: The purpose of the study was to determine the age-specific features of the motor fitness of girls aged 7 to 9. Materials and methods. The study participants were 27 girls aged 7, 40 girls aged 8, and 35 girls aged 9. The children and their parents were informed about all the features of the study and gave their consent to participate in the experiment. The study used such research methods as analysis of scientific and methodical literature, pedagogical observations, motor fitness testing, a probabilistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…The results of the study coincide with the results of Ivashchenko, Iermakov and Khudolii (2021), Kruglov and Khudolii (2022), Khudolii, Golovnin and Bartík (2020) on age and gender peculiarities of development of certain physical abilities in primary school children and their structure.…”
Section: Type and Duration Of Classessupporting
confidence: 86%
“…The results of the study coincide with the results of Ivashchenko, Iermakov and Khudolii (2021), Kruglov and Khudolii (2022), Khudolii, Golovnin and Bartík (2020) on age and gender peculiarities of development of certain physical abilities in primary school children and their structure.…”
Section: Type and Duration Of Classessupporting
confidence: 86%
“…These data and other studies [9,10,11,12] confirm the importance of early intervention and the development of targeted programs aimed at improving coordination abilities and physical activity among younger schoolchildren to maintain their health and well-being in the long term. Furthermore, these and other studies emphasize the importance of an individual approach and the adaptation of physical exercises to the age and gender characteristics of children.…”
Section: Introductionsupporting
confidence: 76%
“…From a health perspective, this decline is a cause for concern, as many studies have shown an inverse correlation between muscle fitness and obesity, cardiovascular disease, and metabolic risk factors in youth (Piek, Bayman & Barnett, 2016;Biernat, Krzepota & Sadowska, 2018;Gjonbalaj et al, 2022). The authors' opinions coincide with the need to develop a comprehensive series of tests that are easy to use to assess motor skills (Masanovic, Gardasevic, Marques et al, 2020;Marchenko & Verdysh, 2021;Kruglov & Khudolii, 2022). This will definitely strengthen the data on longitudinal trends in the physical fitness of children and adolescents around the world.…”
Section: Introductionmentioning
confidence: 89%